2021
DOI: 10.1172/jci.insight.152109
|View full text |Cite
|
Sign up to set email alerts
|

Diminished retinal complex lipid synthesis and impaired fatty acid β-oxidation associated with human diabetic retinopathy

Abstract: METHODS.Retinal tissues were retrieved from postmortem human eyes, including 19 individuals without diabetes, 20 with diabetes but without DR, and 20 with diabetes and DR, for lipidomic study. In a parallel study, serum samples from 28 American Indians with type 2 diabetes from the Gila River Indian Community, including 12 without DR, 7 with mild nonproliferative DR (NPDR), and 9 with moderate NPDR, were selected. A mass-spectrometry-based lipidomic platform was used to measure serum and tissue lipids. RESULTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
(59 reference statements)
3
14
0
Order By: Relevance
“…We have also reported lipidomic analyses of other diabetic complications in the Pimas, including nephropathy 13 and retinopathy. 34 The neuropathy lipidomic signatures from the current study were distinct to both the DKD and the retinopathy signatures, although signatures in all three diabetic complications centered around impaired β‐oxidation. This aligns with our mouse data of tissue‐specific metabolic and lipidomic differences in nerve, kidney, and retina in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…We have also reported lipidomic analyses of other diabetic complications in the Pimas, including nephropathy 13 and retinopathy. 34 The neuropathy lipidomic signatures from the current study were distinct to both the DKD and the retinopathy signatures, although signatures in all three diabetic complications centered around impaired β‐oxidation. This aligns with our mouse data of tissue‐specific metabolic and lipidomic differences in nerve, kidney, and retina in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 56%
“…The Pima Indian type 2 diabetes cohort is long‐established and very homogenous and has been deeply phenotyped for several diabetic complications. 13 , 28 , 34 The great extent of homogeneity minimizes potential confounders, creating a unique opportunity to explore the biology of neuropathy in a type 2 diabetes cohort. Physical examinations and data collection followed well‐specified research protocols, resulting in high‐quality data.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic disturbances induced by DR are mainly related to metabolism of glycolysis, polyols, tricarboxylic acid, amino acids, the urea cycle, and lipids ( Xuan et al, 2020 ). Several observational studies have shown that dyslipidemia, mitochondrial apoptosis, and oxidative stress may be the predominant pathological changes of DR ( Miller et al, 2020 ; Fort et al, 2021 ; Lin et al, 2021 ; Rao et al, 2021 ). Vascular endothelial growth factor (VEGF), HbA1c, low-density lipoprotein cholesterol, myeloperoxidase, and advanced glycation end products (AGEs) are pathogenic factors of DR.…”
Section: Introductionmentioning
confidence: 99%
“…In Fort PE et al.’s study, AC was detected in human retinal tissue and plasma samples. It was found that the abundance of ACs with carbon atom number ≥ 14 decreased in a gradient with the disease state of the subjects (without diabetes, diabetes without DR, and DR) ( 39 ). This finding suggested impaired mitochondrial β-oxidation of retinal FAs in the retina in DR which was consistent with our research.…”
Section: Discussionmentioning
confidence: 99%